Construction Projects as Research Objects–Different Research Approaches and Possibilities - Naaranoja, Marja Kaarina; Kähkönen, Kalle; Keinänen, Marko (Elsevier, 2014)
Research as an activity can mean wide variety of different approaches and their dimensions. Researchers can act as rather passive observers and analyzers by having the current working practices as their research objects. The action research efforts are the ultimate other end. In such efforts researchers act as active change makers by implementing novel trials such as new working practices and their tools. Such trials can fail or be successful but nevertheless the targeted research data is collected as an evidence of the completed effort. Such failures are a real threat for companies and their projects involved in this kind of research. However, more risky action research can be a source for new kind of benefits and competitiveness compared with the more traditional, and wider used, passive observational research. In particular, a sound action research strategy can combine research and development, can speed up targeted changes and can actually mitigate the overall risk of change making. This paper presents a framework of project research strategy and method selection where attention is on degrees of different alternatives and their characteristics. The construction projects and their management represent the industrial context of this paper.
Keywords: pilot projects; construction; research methods; action research; university campus development; fi=Tuotantotalous|en=Industrial Management|